MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PERSAMAAN DAN FUNGSI KUADRAT MELALUI PENGGUNAAN MULTIMEDIA - Endang Rahmijati (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
The goals of this research are: To know the implementation of multimedia at Madrasah Tsanawiyah Negeri 39 Jakarta; To know mathematic learning of equation and square functional of students at Madrasah Tsanawiyah Negeri 39 Jakarta; To know the implementation of multimedia to increase mathematic learning of equation and square functional of Madrasah Tsanawiyah Negeri 39 Jakarta. Type of the research is action research. The subject of this research is the students at Madrasah Tsanawiyah Negeri 39 Jakarta. Implementation of this research is to do 2 cycles, which consist of four activities, that (a) planning, (b) implementing, (c) observing, (d) reflecting. The using of multimedia for students class IX-3 Madrasah Tsanawiyah Negeri 39 Jakarta in the first is difficult. After giving comprehenshive guidance, finally in second cycle runs well. The result of mathematic learning of equation and square functional for students class IX-3 Madrasah Tsanawiyah Negeri 39 Jakarta, before cycle is 65,71% could meet the criteria of success, next in first cycle increase become 68,57%, in the second cycle become 88,57%. Based on the result of research, it can be known the result of mathematic learning of equation and square functional for students class IX-3 Madrasah Tsanawiyah Negeri 39 Jakarta by using multimedia, from the first cycle to the second cycle on going increase, average score is 78,51 increase become 81,49. So there are increase the mathematic learning 2,98. The writer can conclude that there is significant between mathematic learning and multimedia.